THE ROLE OF HEDONIC SHOPPING MOTIVATION AND PROMOTION IN SHAPING ONLINE IMPULSIVE BUYING: THE MEDIATING EFFECT OF SHOPPING ENJOYMENT IN GENERATION Z - Muhammad Anugerah Ramadhan; Muhammad Yani; Mochamad Rizal Yulianto; Rita Ambarwati Sukmono (International Journal of Artificial Intelligence for Digital Marketing, 2025)
Objective: The development of e-commerce has encouraged changes in consumer shopping behavior that was previously offline and is now done online, especially in Generation Z who tend to do Impulsive Buying. This study aims to analyze the influence of Hedonic Shopping Motivation and Promotion on Online Impulsive Buying with Shopping Enjoyment as a mediating variable. Method: The study used a quantitative approach with a survey method of 150 Generation Z respondents who actively shop through e-commerce platforms. The data was analyzed using the Partial Least Square Structural Equation Modeling (PLS SEM) method. Results: The results of the study show that Hedonic Shopping Motivation and Promotion have a positive and significant effect on Online Impulsive Buying. In addition, Shopping Enjoyment has been shown to have a significant effect on Online Impulsive Buying and is able to mediate the influence of Hedonic Shopping Motivation and Promotion on this behavior. Novelty: These findings confirm that emotional aspects, engaging promotions and shopping experiences have an important role in shaping Generation Z's impulsive buying behavior.